2019
DOI: 10.1210/clinem/dgz094
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Ultrasound to Stratify Hormone References in a Cross-Sectional Norwegian Study of Male Puberty

Abstract: Context Testicular growth represents the best clinical variable to evaluate male puberty, but current pediatric hormone references are based on chronological age and subjective assessments of discrete puberty development stages. Determination of testicular volume (TV) by ultrasound provides a novel approach to assess puberty progression and stratify hormone reference intervals. Objective The objective of this article is to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 31 publications
2
21
0
1
Order By: Relevance
“…This, in turn, enabled the calculation of age‐adjusted z ‐scores for each study participant in accordance with our previously published reference chart 26 . We have previously shown that the USTV of 2.7 mL immediately precedes a drastic surge in testosterone levels 35 and our current findings for the associations between testicular volume and anthropometric measurements were corroborated by equivalent findings with regard to serum testosterone. This highlights the co‐occurrence of testicular enlargement and testosterone production.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This, in turn, enabled the calculation of age‐adjusted z ‐scores for each study participant in accordance with our previously published reference chart 26 . We have previously shown that the USTV of 2.7 mL immediately precedes a drastic surge in testosterone levels 35 and our current findings for the associations between testicular volume and anthropometric measurements were corroborated by equivalent findings with regard to serum testosterone. This highlights the co‐occurrence of testicular enlargement and testosterone production.…”
Section: Discussionsupporting
confidence: 87%
“…Blood samples from 299 (92.3%) boys were collected between 0800 and 1400 h and processed according to a protocol for blood sampling and analysis that was previously described 35 . Total testosterone was assayed by LC‐MS/MS as described previously 36 .…”
Section: Methodsmentioning
confidence: 99%
“…Hormone z-scores were interpolated from the “Bergen Growth Study 2” references for male [ 35 ] and female [ 36 ] hormones rendered by the generalized additive model for location, scale and shape (GAMLSS) package in R (R Core Team, Vienna, Austria). Briefly, the LMS method for normalized growth standards [ 37 ] enables the calculation of z-scores for new observations in relation to the smooth (L), mean (M) and coefficient of variation (S) curves.…”
Section: Methodsmentioning
confidence: 99%
“…Justified partitioning criteria were met if the numeric Harris-Boyd z-score exceeded that of the critical z* sample power test, as mathematically outlined previously ( 26-29 ). Continuous hormone reference intervals in relation to chronological age were generated using the CLSI-compliant referenceIntervals package in R (R Development Core Team, Vienna, Austria), based on a moving window of 120 observations as described previously ( 29 ).…”
Section: Methodsmentioning
confidence: 99%